Happy birthday, Molly! : a springtime story - Tripp, Valerie, 1951-; Gaadt, David (Middleton, Wis. : Pleasant Co., 1987)
When an English girl comes to stay at Molly's during World War II, she and Molly learn to bridge their differences and ultimately enjoy a wonderful, mutual birthday party.
"Ages 7-11"--Cover.
580
Accelerated Reader AR
Keywords: World War, 1939-1945 -- United States -- Juvenile fiction; Friendship -- Juvenile fiction